E-Cigarettes in Smoking Cessation and Harm Reduction: A Comprehensive Review of Recent Evidence and Potential Risks - Górka, Mateusz; Kudas, Zuzanna; Szerej, Krzysztof; Wojtkiewicz, Anna; Stec, Weronika; Piekarska, Magda (Quality in Sport, 2024)
The global prevalence of tobacco use has significantly decreased over the years, with projections indicating further decline. However, the rise of new nicotine products suggests that nicotine addiction will remain a major public health issue. Electronic cigarettes (e-cigarettes) are increasingly recognized as potential tools for smoking cessation and harm reduction. This review evaluates the safety and effectiveness of e-cigarettes both as standalone treatments and in combination with other therapies, such as nicotine replacement therapy (NRT), varenicline, cytisine, and behavioral approaches. A comprehensive analysis of studies published over the past decade, including systematic reviews, meta-analyses, and randomized controlled trials, shows that e-cigarettes can enhance smoking cessation rates and reduce tobacco-related harm. They exhibit comparable short-term efficacy to traditional treatments, with promising results in alleviating withdrawal symptoms and lowering smoking rates. However, the long-term safety and effectiveness of combining e-cigarettes with other therapies remain uncertain and require further investigation. Despite their potential benefits, e-cigarettes pose significant safety concerns, underscoring the need for ongoing research to refine cessation strategies and ensure their safe, long-term use. Rigorous evaluation and regulatory oversight are essential to optimize e-cigarettes' role in reducing tobacco harm.